Income transfers and household debt. The advancing collateralization of social policy in the midst of restructuring crises - Lavinas, Lena; Araújo, Eliane; Rubin, Pedro (Brazilian Journal of Political Economy, 2024)
The aim of this article is to address how household debt and contemporary credit markets seem to be the defining elements in the reshaping of social policy both in developing and developed countries. We start off by recalling how the implementation of income policies as the core of a new social protection paradigm has contributed to promote marketbased finance. We take Brazil as a case study to illustrate how this new connection between state guaranteed income policies and credit markets has unfolded resulting in increasing household debt. We show evidence that the connection between household debt and stateprovided monetary benefits is effective and significant. JEL Classification: E44; O11; O54.